Web-based Mental Health Literacy Education Program for Adolescent Students: A Randomized Control Study Protocol - Özlem Özkan; Fatma Şeyda Özbıçakçı (Hemşirelikte Araştırma Geliştirme Dergisi, 2024)

(untitled)
AbstractAim:To establish a randomized controlled trial protocol to evaluate the effectiveness of a Web-based mental health literacy training intervention on RSO knowledge, help-seeking behavior, and stigma attitudes in adolescent students.Design: It is a randomized controlled experimental study with pre-test, post-test, follow-up, control group.Methods: The dependent variables are adolescent knowledge level, attitudes towards seeking psychological help, and mean scores of self-stigma towards seeking help, and the independent variable is web-based education. Participants will be randomly assigned to the control or intervention group. Outcome measures include adolescent knowledge, attitudes, and behavior. Students will be retested after four weeks and three months. The educational content of the six modules will include short animated lesson videos and audio presentations. Opinions of field experts will be obtained for the developed educational content. 100 students will be recruited from a middle and high school. The experimental group will receive a web-based MHL educational intervention, while the control group will not receive any intervention. Data for the study will be collected using the Demographic Data Collection Form, Child and Adolescent Mental Health Literacy Scale (CAMHLS), Attitudes Towards Seeking Psychological Help Scale-Short Form (SPHS-S) and Self-Stigma About Seeking/Getting Psychological Help Scale (SSOSH). Data will be collected at pre-test (t0), 4-week post-test (t2), and 8-week post-test (t3) time points. Repeated measures two-way analysis of variance will be used in data analyses.Conclusion: The unique value of this project will be that the concept of mental health literacy has never been examined before in our society and that a tested teaching material will be prepared and presented to all adolescents, and therefore to families and society, to improve literacy skills.